Design of High Rate Blender Hydraulic Power Pack Unit on Stimulation Vessel – Study Case Stim Star Borneo for Offshore Operations at Delta Mahakam area – East Borneo - Hari Prastowo; Sutopo Purwono Fitri; Raja Oloan Saut Gurning; Sahrul Abidin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Currently application of hydraulic power technology in world industry is still increased. Those phenomenon not only in Industrial field but also in Marine, Onshore and Offshore that use these technologies. Requirement of service in Offshore Delta Mahakam region makes PT. Halliburton Indonesia as a Service Company increase his fleet service. One of the Type Stimulation Vessel Fleets - Stim Star Borneo is planned to improve the service unit of High Rate Water Pack (HRWP) with High Pressure Pump unit plus Gravel Pack Sand (GP) and High Rate Blender Unit as its tools. Blender High Rate is a unit tubular mixing blender driven by hydraulic power, motors blender, sand screw, pump suction and discharge pump that is installed as an unity. In order to analyze those installation, it needs to be planned the section of its system, calculation and specifications of Hydraulic Power Pack Unit for High Rate the Blender. Calculations start from the Operational Requirement Conditions, and continued with Design Block Diagram, P & ID, and also calculations of systems parameter such as Head, RPM, Pipe Diameter, Pipe Thickness, Main Hydraulic Pump, Reservoir Tank and Cooler. The Requirement of Hydraulic Main Pump Power is 950 kW with Electric Motor as prime mover 950 kW. The final result of the design is shown as Layout and Detail drawing in attachment.